PEMBERDAYAAN KEMAMPUAN MEMAHAMI MATEMATIKA TENTANG NILAI TEMPAT MELALUI METODE DEMONSTRASI - Mahfudl Mahfudl (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
This study aims to describe the improvement of the mathematical abilities of place value with the empowerment of demonstration methods in the second grade students of SDN Ngujungrejo. This classroom action research was conducted in the second grade of SDN Ngujungrejo. The results showed that the demonstration method was able to improve the understanding of place value in the second grade students of SDN Ngujungrejo. Empowerment of the ability of the students to understand the mathematics of grade 2 Ngujungrejo SDN about the value of the place, then student achievement also increases.